On Keep and Keep on: A Corpora-based Analysis - Kang, Namkil (Advances in Social Sciences Research Journal, 2022)
The main goal of this paper is to provide a comparative analysis of keep and keep on in the TV Corpus and the British National Corpus. With respect to the TV Corpus, it is interesting to note that keep was favored over keep on from the 1950s to the 2010s. A further point to note is that keep and keep on reached a peak (28,586 tokens vs. 1,303 tokens) in the 2010s. In addition, it is worth pointing out that keep was always preferable to keep on from the 1950s to the 2010s. With respect to the BNC, it is probably worthwhile pointing out that keep is 71.42% the same as keep on in the seven genres of the BNC. When it comes to the Euclidean distance between keep and keep on, the former is the nearest from the latter in the fiction genre, whereas the former is the furthest from the latter in the spoken genre. Quite interestingly, the BNC clearly shows that keep going and keep on going are the most preferred (430 tokens vs. 24 tokens) by the British. Finally, it is significant to note that 43.58% of thirty nine gerunds are the collocations of both keep and keep on.